Reconstruction of Ethnopedagogy: The Implementation of Teaching Materials Based on the Local Wisdom of the Talang Mamak Tribe in Enhancing Students’ Morality and Ethics - Yelvia Septi Mayenti; Kama Abdul Hakam; Elly Malihah; Mupid Mupid (Newinera Publisher, 2026)
This study aims to analyze the process and outcomes of implementing character education teaching materials that integrate the local wisdom of the Talang Mamak Tribe (STM) in order to mitigate moral degradation among adolescents. The research adopts a Mixed Methods approach with an Exploratory Sequential design, integrating qualitative ethnographic exploration and quantitative quasi-experimental testing. The qualitative phase involved participatory observation and in-depth interviews with key community informants, focusing on fundamental rituals such as Begawai, Bulian, and death ceremonies to extract core ethical values. These values were reconstructed into teaching materials that combine the philosophy of Alam Takambang Jadi Guru with the National Curriculum, bridging traditional wisdom and contemporary educational relevance. The quantitative phase tested the effectiveness of the teaching materials using a quasi-experimental design with a nonequivalent control group. Data analysis employing paired and independent sample t-tests, as well as N-gain calculations, revealed statistically significant improvements in moral self-efficacy and ethical behavior. The experimental group achieved an N-gain score of 0.6257 (high category) and 100% completeness above the Minimum Competency Criteria (KKM 75), indicating strong cognitive and affective internalization of local values. Findings suggest that ethnopedagogical teaching materials serve as an effective instrument for pattern maintenance (latency), internal boundary management, and value deformalization, allowing students to navigate ethical challenges in modern and digital contexts while remaining rooted in cultural identity. The study confirms that integrating local wisdom into formal education is not merely a cultural preservation effort but a forward-looking strategy for character formation, moral resilience, and social cohesion.